Interdisciplinary aesthetics when science and drama are linked - Prain, Vaughan; Tytler, Russell; Raphael, Jo (Frontiers in Education, 2023)
There is a strong tradition of viewing these two subjects as mutually enhancing, but aesthetic aspects of this interplay are less studied. In this paper we define disciplinary aesthetics as appreciation and enjoyment of the what and how of learning within and across both subjects. Drawing on Peirce's semiotic theory of signs, we claim that meaning-making from, with and through signs and sign systems (a) is fundamental to learning in both subjects and (b) constitutes a key feature of valuing and contributing to an aesthetic taste for both subjects. We illustrate these claims through examples drawn from secondary and tertiary learning.